2018
DOI: 10.4158/accr-2018-0095
|View full text |Cite
|
Sign up to set email alerts
|

Successful Pregnancy on a Gluten-Free Diet in a Woman with Seven Miscarriages and Nonceliac Gluten Sensitivity

Abstract: Objective: To describe a case in which a glutenfree diet led to a successful full-term delivery in a woman with recurrent miscarriages and nonceliac gluten sensitivity (NCGS).Methods: Reduced incidences of spontaneous abortions have been reported in patients with celiac disease who adhere to a gluten-free diet, but little is known about improvement in reproductive issues in women with NCGS. We present a case of a woman with multiple miscarriages who improved on a gluten-free diet.Results: A 33-year-old woman p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The patients with CeD can delayed menarche, early menopause, recurrent abortions, infertility, intrauterine growth retardation, and low birth weight (preterm and small for gestational age babies)[ 66 , 67 ]. Additionally, reports have suggested that women with infertility have conceived after initiation of GFD with a diagnosis of CeD[ 68 , 69 ]. Furthermore, there are multiple studies reporting the prevalence of CeD in women with infertility in women who had been investigated for the causes of infertility earlier (unexplained or idiopathic infertility) and those women with infertility who were never investigated for infertility (all cause infertility).…”
Section: Possible Conditions For Screening For Cedmentioning
confidence: 99%
“…The patients with CeD can delayed menarche, early menopause, recurrent abortions, infertility, intrauterine growth retardation, and low birth weight (preterm and small for gestational age babies)[ 66 , 67 ]. Additionally, reports have suggested that women with infertility have conceived after initiation of GFD with a diagnosis of CeD[ 68 , 69 ]. Furthermore, there are multiple studies reporting the prevalence of CeD in women with infertility in women who had been investigated for the causes of infertility earlier (unexplained or idiopathic infertility) and those women with infertility who were never investigated for infertility (all cause infertility).…”
Section: Possible Conditions For Screening For Cedmentioning
confidence: 99%